The Role of Electoral Interests in the National Distribution of EU Covid-19 Funds - Romy Hansum (JCMS: Journal of Common Market Studies, 2024)
Expectations are high regarding the impact of the extensive Covid-19 crisis support `Next Generation EU'. Mixed experiences from established EU distributive policies indicate, though, that ultimate policy outcomes largely depend on national implementation decisions. This article scrutinises vote-buying strategies according to which domestic governments exploit the largely autonomous national distribution of EU funds to target certain constituencies. To study national strategies, the analysis takes advantage of the extraordinary leeway given to domestic governments in distributing REACT-EU funds, part of Next Generation EU. The encompassing quantitative analysis covers a large sample of member states and committed funds. The regression results provide no support that national governments distribute REACT-EU funds to politically opportune regions. In a departure from most previous analyses focusing on specific member states, these findings suggest that vote buying is not the dominant strategy in the national implementation of all EU funds.
Keywords: 330; Covid-19; EU funds; implementation; NGEU; vote buying